Transitions of two magnetic interaction states in dinuclear Dy(iii) complexes via subtle structural variations. Issue 3 (19th December 2016) - Zhang, Kun; Liu, Dan; Vieru, Veacheslav; Hou, Lei; Cui, Bin; Guo, Fu-Sheng; Chibotaru, Liviu F.; Wang, Yao-Yu
Abstract : Herein we explored the transitions of two magnetic interaction states (antiferromagnetic or ferromagnetic) upon structural variations in two dinuclear Dy(iii ) complexes. Abstract : Herein we explored the transitions of two magnetic interaction states (antiferromagnetic or ferromagnetic) upon structural variations in two dinuclear Dy(iii ) complexes.